Principle of the helical and nonhelical dynamo and the α effect in a field structure model - Park, Kiwan (The astrophysical journal, 2019)
We demonstrate the conversion process of helical (nonhelical) kinetic energy into magnetic energy using a field-structure model based on the magnetic induction equation. This approach aims to explain the generation, transport, and conservation of magnetic helicity dependent on a forcing method such as kinetic or magnetic forcing. When a system is driven by helical kinetic or magnetic energy, two kinds of magnetic helicities with opposite signs are induced. Then, asymmetric competing processes between them determine the dominant magnetic helicity. Also, the model shows that the conservation of magnetic helicity is related to a common current density and antiparallel magnetic fields in the large- and small-scale regimes. In addition to the intuitive method, we suggest an analytical method to find the α and β coefficients using temporally evolving large-scale magnetic energy and magnetic helicity. The method implies that the α effect and its quenching are generally consistent with the conventional theory. However, the β coefficient implies that the role of kinetic energy in a dynamo may be somewhat different from our conventional understanding. We also show how the kinetic energy near the viscous scale can suppress the dynamo process when the magnetic Prandtl number (Pr M ) is small. We verify this using simulation results. Finally, using the α 2 effect and differential rotation effect, we suggest a solar dynamo model that explains the periodic magnetic evolution in the Sun.